2013
DOI: 10.1016/j.febslet.2013.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methyl transferases‐3 and ‐5 increase cell surface expression of cardiac sodium channel

Abstract: a b s t r a c tThe a-subunit of the cardiac voltage-gated sodium channel (Na V 1.5) plays a central role in cardiomyocyte excitability. We have recently reported that Na V 1.5 is post-translationally modified by arginine methylation. Here, we aimed to identify the enzymes that methylate Na V 1.5, and to describe the role of arginine methylation on Na V 1.5 function. Our results show that protein arginine methyl transferase (PRMT)-3 and -5 methylate Na V 1.5 in vitro, interact with Na V 1.5 in human embryonic k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…These results are consistent with increased methylation resulting in enhanced amplitude of Nav current. In the case of Nav1.5, the authors presented data supporting increased cell surface expression of Nav1.5 channels as a mechanism contributing to the increased Nav current (54). We found in samples from mammalian brain that increased arginine methylation was associated with decreases in Nav1.2 phosphorylation.…”
Section: Discussionsupporting
confidence: 57%
“…These results are consistent with increased methylation resulting in enhanced amplitude of Nav current. In the case of Nav1.5, the authors presented data supporting increased cell surface expression of Nav1.5 channels as a mechanism contributing to the increased Nav current (54). We found in samples from mammalian brain that increased arginine methylation was associated with decreases in Nav1.2 phosphorylation.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have suggested that methylation of some ion channel proteins could affect their activities/functions (Beltran-Alvarez et al, 2013; Sariban-Sohraby et al, 1984). To investigate a potential interaction between KCNQ2 and Prmt1, co-immunoprecipitation experiments were conducted with HEK293T cells.…”
Section: Resultsmentioning
confidence: 99%
“…5, A and B), six are associated with the plasma membrane, including the strongest binder, NHERF2. Importantly, PRMT5 has been shown to methylate a number of proteins that are membraneassociated (37,38). We thus surmised that the C terminus of PRMT5 was responsible for localizing it to the intracellular side of the plasma membrane.…”
Section: -3-3/pdz Switchingmentioning
confidence: 99%